NEUROMYTH: BETWEEN MYTH AND REALITY IN PHILOSOPHICAL PERSPECTIVE - Sri Maryanti; Nahadi Nahadi; Sjaeful Anwar (Bajang Institute, 2023)
Neuromyths are erroneous beliefs about the brain and how it works. Neuromyths often appear in mass media, popular literature, and even in formal education. Neuromyths can have negative impacts, such as causing diagnostic and therapeutic errors, as well as hindering research and development in the field of neuroscience. In this paper, the author will discuss neuromyths from a philosophical perspective. The author will review how neuromyths emerge and develop, as well as how neuromyths can be criticized from a philosophical perspective. The author will also discuss the implications of neuromyths for society and education.